2015
DOI: 10.5194/amt-8-483-2015
|View full text |Cite
|
Sign up to set email alerts
|

Empirical validation and proof of added value of MUSICA's tropospheric δD remote sensing products

Abstract: Abstract. The project MUSICA (MUlti-platform remote Sensing of Isotopologues for investigating the Cycle of Atmospheric water) integrates tropospheric water vapour isotopologue remote sensing and in situ observations. This paper presents a first empirical validation of MUSICA's H 2 O and δD remote sensing products, generated from groundbased FTIR (Fourier transform infrared), spectrometer and space-based IASI (infrared atmospheric sounding interferometer) observation. The study is made in the area of the Canar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 35 publications
0
63
0
Order By: Relevance
“…2.5. The technical details for this comparison, like the need for applying the averaging kernels to the reference profiles, are the same as for the exemplary study of Schneider et al (2015). The error bars on the reference data are largely due to the unknown humidity and δD values above the aircraft's ceiling altitude.…”
Section: Ndacc/ftirmentioning
confidence: 95%
See 4 more Smart Citations
“…2.5. The technical details for this comparison, like the need for applying the averaging kernels to the reference profiles, are the same as for the exemplary study of Schneider et al (2015). The error bars on the reference data are largely due to the unknown humidity and δD values above the aircraft's ceiling altitude.…”
Section: Ndacc/ftirmentioning
confidence: 95%
“…In an exemplary study with the previous MUSICA MetOp/IASI retrieval version, Schneider et al (2015) reported a bias between the IASI δD product and the δD reference of about 60 ‰ (see Fig. 11 therein).…”
Section: Metop/iasimentioning
confidence: 99%
See 3 more Smart Citations